An OFDMA based concurrent multiuser MAC for upcoming IEEE 802.11ax - Qiao Qu; Bo Li; Mao Yang; Zhongjiang Yan (2015 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2015)
Recently, IEEE drew up a new task group named TGax to draft out the standard IEEE 802.11ax for next generation WLANs. However, the average throughput is very low due to the current medium access control (MAC) protocol. A promising solution for this problem is to draw Orthogonal Frequency Division Multiple Access (OFDMA) into IEEE 802.11ax to enable multiuser access. The key challenges of adopting OFDMA are synchronization and overhead reduction. In this paper, we propose an OFDMA based Multiple Access for IEEE 802.11ax (OMAX) protocol to solve both two challenges above. The whole channel physical channel sensing and fast backoff are adopted to ensure synchronization, while enhanced RTS/CTS mechanism and new frame structure are designed to reduce overhead. Moreover, the mathematic model of OMAX is formulated, and the performance of OMAX is analyzed. The analysis and simulation result indicate that the proposed OMAX protocol increases the throughput to 160%.